STRATEGI CORPORATE IMAGE DALAM MENINGKATKAN KEPUASAN PELANGGAN DI MEDIA SOSIAL TIKTOK - Kharisma Dewi, Hocky Nis; Suryasuciramdhan, Arfian; Aisyah, Gisella; Fariji, Firdy Ahmad; Ramadhan, Rhizqi Dwiputra (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
Currently, the business world is experiencing very rapid growth. causing various industrial sectors to compete with each other, including the cosmetics industry. In this era, the cosmetics industry not only focuses on beauty, but also functions as skin care. Of the various types of skin care that are currently popular, namely facial masks, they sell very quickly in the market. Among the skin care brands that exist today, skintific has emerged as a well-known skincare brand that is on the rise. Research Approach In this study, we used a descriptive qualitative research method. according to (Bungin, 2008) Qualitative research is research that aims to understand social phenomena from the perspective of participants or research subjects by prioritizing meaning, process, and contextual understanding. Qualitative methods are a set of ways to analyze and understand the meaning that is relevant to individuals or groups in the context of humanitarian or social problems. This qualitative research is exploratory, which means it is the first step in research with a broad scope. Exploratory research is very important because it can produce a strong foundation for obtaining detailed ideas related to the main problem, as well as for developing existing research. Keywords: Image brand, tiktok, digital marketing strategy, skincare, skintific.